ANALISIS RISIKO PROYEK PEMBANGUNAN GEDUNG PEMERINTAHAN DENGAN METODE SIMULASI MONTE CARLO - Theophila Hadinata, Thalia
As an industrial engineer, the biggest constraints in construction project are in project management science, which takes a big part in managing two of the three important project constraints, namely time and cost. PT Haka Utama is currently in the project planning stage for the construction of a government building which has the scope of the main building, guard post, power house, as well as roads, courtyards and drainage with a value of Rp50.278.931.376,43 before tax. After the project work arrangements were made, the project work duration which was initially 315 days was shortened into 273 days. However, with the time for work proposals decreasing, it is necessary to carry out a project risk analysis, to ensure the system can accommodate if delays occur. For government project work, delays often occur, therefore, the project owner is still able to accept a time and cost risk of 20%. Meanwhile, based on the Monte Carlo simulation for the 64 risks found, the risk value of additional costs that could occur was 26.7% and the risk of additional time that could occur was 67.4%. Therefore, mitigation is carried out which is designed to reduce the risk value by one level. The result of using risk mitigation suggestions is a reduction in risk effects, namely an additional cost of 10.2% and an additional time of 33.3%. In actual figures, there will be an addition of Rp5,119,042,028.10 and a delay of 91 days. Even though the value of the time delay is beyond what the project owner accepts, it can still be accommodated by using additional workforce, so it can be concluded that the mitigation suggestions are acceptable.